Influence of Tiktok Marketing Content And Halal Awareness on Purchasing Decisions With Bpom Attributes as Intervening - Indriyana Eka Salasbila; Dadan Ramdhan (International Journal of Education, Information Technology, and Others, 2022)
The emergence of the Tiktok application makes consumers spend as much as 52 minutes to see the content on the application, one of which is the world of beauty. For business people, this application is very profitable because it can increase interest by as much as 70% every month. With the large number of Muslims in Indonesia, Muslim women are faced with several things before buying a beauty product such as its halalness and the content in it. One of them is the BPOM attribute listed on the product as information to consumers. However, LPPOM MUI stated that there are still many people who do not understand about the BPOM regulation because the public thinks that when it is certified bpom then it is halal, but not necessarily. This study was conducted to look at the influence of Tiktok marketing content and consumer halal awareness on purchasing decisions to be mediated by BPOM Attributes on Scarlett Whitening products. This type of research uses quantitative methods with descriptive statistical approaches, multiple linear analysis and path analysis (to find out the influence of mediation). The study used data from 125 Muslim respondents with the dissemination of questionnaires in the form of likert scales as primary data. Data processing uses SPSS Version 25 and sobel tests to calculate the influence of mediation. The results of this study show that the influence of (1) Tiktok marketing content has a direct effect on BPOM's attributes. (2) Halal Awareness has no influence on BPOM attributes. (3) Tiktok marketing content directly affects purchasing decisions. (4) Halal awareness has no influence on purchasing decisions. (5) BPOM attributes directly affect purchasing decisions. (6) BPOM attributes have no mediating influence on Tiktok's marketing content on purchasing decisions. (7) BPOM attributes do not have a mediating effect on halal awareness of purchasing decisions